Prognostic value of the preoperative albumin–globulin ratio in patients with upper urinary tract urothelial carcinoma treated with radical nephroureterectomy: results from a large multicenter international collaboration. (27th February 2021) - Miura, Noriyoshi; Mori, Keiichiro; Laukhtina, Ekaterina; Schuettfort, Victor M; Abufaraj, Mohammad; Teoh, Jeremy Y C; Luzzago, Stefano; Stolzenbach, Franziska; Deuker, Marina; Karakiewicz, Pierre I; Briganti, Alberto; Enikeev, Dmitry V; et al.
Abstract: Objective: To assess the value of preoperative albumin to globulin ratio for predicting pathologic and oncological outcomes in patients with upper tract urothelial carcinoma treated with radical nephroureterectomy in a large multi-institutional cohort. Materials and Methods: Preoperative albumin to globulin ratio was assessed in a multi-institutional cohort of 2492 patients. Logistic regression analyses were performed to assess the association of the albumin to globulin ratio with pathologic features. Cox proportional hazards regression models were performed for survival endpoints. Results: The optimal cut-off value was determined to be 1.4 according to a receiver operating curve analysis. Lower albumin to globulin ratios were observed in 797 patients (33.6%) compared with other patients. In a preoperative model, low preoperative albumin to globulin ratio was independently associated with nonorgan-confined diseases (odds ratio 1.32, P = 0.002). Patients with low albumin to globulin ratios had worse recurrence-free survival ( P < 0.001), cancer-specific survival ( P = 0.001) and overall survival ( P = 0.020) in univariable and multivariable analyses after adjusting for the effect of standard preoperative prognostic factors (recurrence-free survival: hazard ratio (HR) 1.31, P = 0.001; cancer-specific survival: HR 1.31, P = 0.002 and overall survival: HR 1.18, P = 0.024). Conclusions: Lower preoperative albumin to globulin ratio is associated with locally advanced disease and worse clinical outcomes in patients treated with radical nephroureterectomy for upper tract urothelial carcinoma. As it is difficult to stage disease entity, low preoperative serum albumin to globulin ratio may help identify those most likely to benefit from intensified care, such as perioperative systemic therapy, and the extent and type of surgery. Abstract : Low preoperative albumin to globulin ratio is associated with locally advanced disease and worse clinical outcomes in patients with upper tract urothelial carcinoma treated with radical nephroureterectomy.